The Use of The Outdoor Study Method in Poetry Writing Skills - Rahallus, Nevyanti Jeqlyn (Universitas Pattimura, 2023)
This research focuses the use of poetry writing skills on class X students of SMA Negeri 7 Ambon. The purpose of the research conducted was to describe the outdoor study method at SMA Negeri 7 Ambon. This research is aqualitative research that produces descriptive data. The data collection technique uses the listening technique along with the follow-up techniques, note-taking techniques and interviews. Based on the results of the writing, the advantages and disadvantages of the outdoor study method were found. In using the method outdoor study on the use of poetry writing skills, it can be concluded that the influence of the method outdoor study in the use of poetry writing skills, not everyone has accepted or understood it. This is evidenced by the fact that some people have no interest in writing poetry and their vocabulary is limited. In addition, the use of the method outdoor study it was also successfully used by students of SMA Negeri 7 Ambon, in that they began to like or be interested in getting to know and creating poetry, and their insights began to open up to be able to produce beautiful words when creating poetry outside the classroom.